Risk factors for young people not being in education, employment or training (NEET): Longitudinal analyses over a 10 year follow up period in Scotland - Everington, Dawn; Feng, Zhiqiang; Ralston, Kevin; Dibben, Chris (International Journal of Population Data Science, 2018)
Background The high level of young people who are NEET has been an important long-standing issue in Scotland. Having been NEET has several long term detrimental effects. Identifying risk factors of becoming NEET may inform interventions aimed at reducing the overall number of NEETs. Data We used the Scottish Longitudinal Study (SLS) - a 5.3% sample of Scotland’s population based around the 1991, 2001 and 2011 Censuses. The SLS include vital event data and since 2007, school census data. Census data are available for family members of the SLS sample. We followed two cohorts to age 16-19 years: the first cohort included 6-9 years old at the 1991 census and the second 6-9 years old at the 2001 census. Methods We used logistic regression to investigate whether NEET status was associated with individual, family and household characteristics measured 10 years previously, school qualifications and behaviour, local area characteristics and whether they had had a teenage pregnancy. Finding Many factors were associated with the likelihood of being NEET - highest school qualification and behaviour, teenage pregnancy (females), household characteristics and living in an area having a relatively high level of NEETs.